Model tata kelola keuangan sebagai upaya keberlangsungan usaha dimasa pandemic covid-19 - Oktavia, Dwi Dayanti; Ratnasari, Ike (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Good financial management is the main key for a business to survive and grow in any situation and condition. MSMEs as one of the types of businesses that contribute the most to national income and can increase economic growth in Indonesia; however, many are still unaware of the importance of managing their business finances. This is due to a lack of understanding regarding financial governance. For this reason, a financial governance method is needed to help or facilitate MSME financial management in managing their business. The research objective is to find out problems with MSME financial governance by utilizing the financial portfolio method to make it easier for MSME actors to manage their finances so that they can provide good information related to finance to provide benefits for MSME financial management. This study uses explorative qualitative analysis methods with participatory observation techniques. Primary and secondary data sources. Based on the study's results, it was found that the informants in financial management, in general, had been managed very well, as seen by recording every financial transaction of the business being carried out. The management carried out by MSMEs is to make notes in the form of a financial portfolio.